Size effect in particle debonding: Comparisons between finite fracture mechanics and cohesive zone model. (June 2019) - Gentieu, Timothée; Jumel, Julien; Catapano, Anita; Broughton, James
The present study aims at describing the debonding phenomenon of a particle embedded in an elastic matrix. Two types of fracture mechanics approaches are developed and compared in this context. The phenomenon is analytically described using a finite fracture mechanics approach, while numerical simulations are performed using a cohesive zone model to describe the decohesion process. Both methods rely on two mechanical parameters: the interface strength, σmax and the fracture energy, Gc, of the interface. Both modelling approaches produce results that show larger particles tend to debond before smaller ones although noticeable differences are observed, especially concerning the relationship between the critical load and the particle radius: in the framework of the FFM, the critical load is inversely proportional to the square root of the particle radius, while when using CZM, the critical load is inversely proportional to the particle radius.